Analysis of MSME Players of Creative Economy Culinary Subsector in Bengkalis City - Julia Ningsih; wan Junita Raflah (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
This study aims to determine what Kinds of Culinary ,characteristics ,creativity, and the Structure-Conduct-Performance (SCP) approach. This study used a qualitative descriptive method with the object of research on MSME players. The sampling technique of this study used a stratified random sample method with a total of 40 samples. Data collection techniques in this study using documentation and interview methods. The results of this study 50% of MSME players are 41-50 years old, 47,5% MSME players have a high school background as their last education, 27.5% have been in business for 1-2 years. Based on the SCP approach, the culinary business model in Bengkalis City  is independent, MSME players in Bengkalis City set prices looking at price information from competitors, in promotion tools 75% of MSME players put in stalls and the performance of MSME players is 32.5% monthly income ranges from IDR 2.000.000 - IDR 5.000.000